Investigaciones serológicas de brucelosis en animales y humanos - Pontón Rodríguez, Grace Ailis (2021)
The present work was based on the review and analysis of serological investigations of brucellosis between animals and humans that have been carried out worldwide and in Ecuador. Brucellosis is a public health problem, as it is a zoonotic disease that negatively affects the health of workers associated with the management of cattle herds. According to research carried out by Delgado & Valencia, 2018, in which blood samples were collected in 20 livestock farms, obtaining blood serum from 198 animals (of these, 172 corresponded to cows). The Rose Bengal test was performed and the positive cases confirmed by competitive ELISA, the last test with which the prevalence of the disease was calculated. A seroprevalence of 0% was obtained in males and 5.81% in females. The prevalence of brucellosis at the farm level was 40%. (Valencia, 2017), in his study Prevalence of brucellosis in slaughterers, veterinarians and administrators in the Esmeraldas, Atacames and Quinindé litters of the Esmeraldas province, using the rose bengal test (RB) ”, describes that (53) people were sampled in the canton Esmeraldas, slaughterers 27, Veterinarians 1 and Administrators 2, not all use their full protective equipment in their work and are not aware of the possible risks to which they are exposed, due to contagion from the animals they slaughter. In the Rose Bengal Analysis, the results of the analysis were negative in the 53 sampled. 66.67% of the personnel who work in the slaughterhouse of the municipality of Esmeraldas if they consume fetuses, which increases the risk of contagion and 33.33% do not consume it,